2015
DOI: 10.1128/aem.00832-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel N4 Bacteriophages Prevail in the Cold Biosphere

Abstract: bColiphage N4 is a lytic bacteriophage discovered nearly half a century ago, and it was considered to be a "genetic orphan" until very recently, when several additional N4-like phages were discovered to infect nonenteric bacterial hosts. Interest in this genus of phages is stimulated by their unique genetic features and propagation strategies. To better understand the ecology of N4-like phages, we investigated the diversity and geographic patterns of N4-like phages by examining 56 Chesapeake Bay viral communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…Bacteriophages are viruses which have the ability to multiply only in bacterial cells, and they are detectable almost everywhere where live bacteria exist (they have been isolated from all environments and ecological niches, e.g., inland waters, hot springs, salt water, soil, cold water) ( Lin et al, 2010 ; Zheng et al, 2013 ; Zhan et al, 2015 ). It is estimated that in the biosphere there are approximately 10 30-31 phages ( Hendrix et al, 1999 ; Hendrix, 2002 ), which is 10-fold higher than the total number of bacterial cells ( Abedon et al, 2011a ).…”
Section: State Of the Artmentioning
confidence: 99%
“…Bacteriophages are viruses which have the ability to multiply only in bacterial cells, and they are detectable almost everywhere where live bacteria exist (they have been isolated from all environments and ecological niches, e.g., inland waters, hot springs, salt water, soil, cold water) ( Lin et al, 2010 ; Zheng et al, 2013 ; Zhan et al, 2015 ). It is estimated that in the biosphere there are approximately 10 30-31 phages ( Hendrix et al, 1999 ; Hendrix, 2002 ), which is 10-fold higher than the total number of bacterial cells ( Abedon et al, 2011a ).…”
Section: State Of the Artmentioning
confidence: 99%
“…Using a pair of group‐specific primers based on the DNA polymerase gene, N4‐like phages were detected in natural samples. N4‐like phages are highly diverse and prevalent in the winter Chesapeake Bay (Zhan et al ., ). A global survey on their distribution indicated that N4‐like phages appear to be restricted to the high latitude marine environment and several Antarctic lakes, especially Organic Lake and Ace Lake, where roseobacters are prevalent (Yau et al ., ; Zhan et al ., ).…”
Section: Ecology Of Roseophages and Their Impact On Hostsmentioning
confidence: 97%
“…N4‐like phages are highly diverse and prevalent in the winter Chesapeake Bay (Zhan et al ., ). A global survey on their distribution indicated that N4‐like phages appear to be restricted to the high latitude marine environment and several Antarctic lakes, especially Organic Lake and Ace Lake, where roseobacters are prevalent (Yau et al ., ; Zhan et al ., ). The presence of DSS3Φ8 in these Antarctic lakes further supports the tight co‐existence of roseobacters and their phages (Zhan et al ., ).…”
Section: Ecology Of Roseophages and Their Impact On Hostsmentioning
confidence: 97%
“…Bacteriophages are viruses which have the ability to multiply only in bacterial cells, and they are detectable almost everywhere where live bacteria exist [ 1 ]. The environment populated by bacterial hosts such as soil, sewage, and animal secretions are unique source of all types of phages, offering the possibility to isolate them for therapeutic purposes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%